2022
DOI: 10.1021/acs.jafc.2c00631
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Bioactivity of MicroRNAs of Plant-Derived Exosome-Like Nanoparticles and Milk-Derived Extracellular Vesicles

Abstract: MicroRNA (miRNA) is a class of small noncoding RNA involved in physiological and pathological processes via the regulation of gene expression. Naked miRNAs are unstable and liable to degradation by RNases. Exosome-like nanoparticles (ELNs) secreted by plants and extracellular vesicles (EVs) found in milk are abundant in miRNAs, which can be carried by ELNs and EVs to target cells to exert their bioactivities. In this review, we describe the current understanding of miRNAs in plant ELNs and milk EVs, summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…Current studies have shown that exosomes are widely found in foodstuffs, including vegetables, fruits [9], and milk [19]. However, the presence and function of exosomes in meat products remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that exosomes are widely found in foodstuffs, including vegetables, fruits [9], and milk [19]. However, the presence and function of exosomes in meat products remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that exosome is widely found in many foodstuffs such as vegetable, fruit [9], milk [19], etc,. However, few studies on the exosomes in meat products have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies suggest that a common dietary polyphenol EGCG regulates macrophage polarization via miRNAs that other cells secrete in response to EGCG stimulation, indicating a novel possible mechanism of the physiological regulation induced by dietary chemicals. In addition, plant-exosome-like nanovesicles and milk-derived extracellular vesicles are collecting attention for their physical stability and biosafety even though, here, an in-depth investigation of the roles of miRNA from various foods is still warranted to solve these challenges [ 115 ]. Taking this evidence into consideration, food intake can modulate immune systems to maintain healthy conditions by exosomes present in food or exosomal intercellular communication initiated from the stimulation by dietary compounds.…”
Section: Perspective and Conclusionmentioning
confidence: 99%